Analisis Kandungan Sodium pada Minuman Berkarbonasi yang Ada Di Kota Makassar - Melli Fitriani (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2017)
The background of this study is the habit of people who like to consume carbonated beverages in excess without paying attention to the negative impact on health. One of the elements contained in carbonated beverages is sodium, which when consumed in excess can cause various diseases. The purpose of this study was to determine the sodium content in carbonated beverages in Makassar. The type of this research is laboratory observation with quantitative analysis technique. Samples examined in the form of ten brands of carbonated beverages in Makassar are examined by Atomic Absorption Spectrophotometer (SSA) method. This research was conducted on 25 to 27 June 2016 at Health Laboratory Installation Laboratory of Center of Health Laboratory of Makassar. The results showed that the ten brands of drinks have sodium content in accordance with the reference value of BPOM is 480 mg / saji. The average value of sodium content obtained 24.63 mg / 100 ml or 79.77 mg / saji with the highest content of 42.21 mg / 100 ml or 139.29 mg / s serving on samples of T brands and the lowest content of 12.97 mg / 100 ml or 32,43 mg / saji on sample of GS brand. Sodium in carbonated beverages derives from several ingredients into the composition of the manufacture of this beverage, such as NaCl contained in water, sodium benzoate, trisodium citrate, and others.